Visible spectrophotometric determination of Cefadroxil using ethyl acetoacetate and formaldehyde reagents - Susidarti, Ratna Asmah; Rianti, Andrih; Martono, Sudibyo (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
Visible spectrophotometric method can be used to determine cefadroxil in the pharmaceutical dosage form. The reaction of cefadroxil with the condensation product of 2 mol ethyl acetoacetate and 1 mol formaldehyde in acidic condition (pH 3,5) at 45Â°C for 20 minutes yielded yellow product giving absorption at 367 nm. The concentration of Cefadroxil was calculated by using standard curve Y = 1.6063 X + 0.1634, r = 0.9932, p = 0,001 and Vxo = 9,7%. Determination of cefadroxil capsule â€Xâ€ (562.4 mg/capsule) showed that the concentration of cefadroxil observed is 490.5 mg/capsule (CV = 0.89%) and recovery value is 102.88% (CV = 0.67%). Key words: visible spectrophotometry, Cefadroxil, ethyl acetoacetate, formaldehyde